2011
DOI: 10.1523/jneurosci.1171-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 3,4-Methylenedioxymethamphetamine (MDMA) EnantiomersIn Vitroand in the MPTP-Lesioned Primate:R-MDMA Reduces Severity of Dyskinesia, WhereasS-MDMA Extends Duration of ON-Time

Abstract: 1-methyl-4-phenyl-1,2,3,6tetrahydropyridine) administration. Motor disability, including parkinsonism and dyskinesia, and duration of antiparkinsonian benefit (ON-time) were evaluated. After the administration of R-MDMA (3 and 10 mg/kg), the severity of peak-dose dyskinesia was decreased (by 33 and 46%, respectively; p Ͻ 0.05); although total ON-time was unchanged (ϳ220 min), the duration of ON-time with disabling dyskinesia was decreased by 90 min when compared to L-DOPA alone (69% reduction; p Ͻ 0.05). S-MDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 49 publications
(46 reference statements)
2
34
0
Order By: Relevance
“…It should be noted though that both clozapine and quetiapine bind to several other serotonergic and nonserotonergic receptors (Huot et al, 2011a) and that, although their antidyskinetic efficacy is usually attributed to antagonizing 5-HT 2A receptors, a contribution of these other targets cannot be excluded, therefore limiting the interpretation of these pharmacological studies. More selective compounds such as the Renantiomer of 3,4-methylenedioxymethamphetamine (MDMA) (Huot et al, 2011c) and pimavanserin (ACP-103) (Vanover et al, 2008) also alleviated LID in the MPTP-lesioned NHP. In clinical settings, clozapine (Durif et al, 2004) as well as the more selective 5-HT 2A antagonists ritanserin (Maertens de Noordhout and Delwaide, 1986;Meco et al, 1988) and pimavanserin (Roberts, 2006) all alleviated dyskinesia.…”
Section: B 5-ht 2a Receptorsmentioning
confidence: 99%
“…It should be noted though that both clozapine and quetiapine bind to several other serotonergic and nonserotonergic receptors (Huot et al, 2011a) and that, although their antidyskinetic efficacy is usually attributed to antagonizing 5-HT 2A receptors, a contribution of these other targets cannot be excluded, therefore limiting the interpretation of these pharmacological studies. More selective compounds such as the Renantiomer of 3,4-methylenedioxymethamphetamine (MDMA) (Huot et al, 2011c) and pimavanserin (ACP-103) (Vanover et al, 2008) also alleviated LID in the MPTP-lesioned NHP. In clinical settings, clozapine (Durif et al, 2004) as well as the more selective 5-HT 2A antagonists ritanserin (Maertens de Noordhout and Delwaide, 1986;Meco et al, 1988) and pimavanserin (Roberts, 2006) all alleviated dyskinesia.…”
Section: B 5-ht 2a Receptorsmentioning
confidence: 99%
“…The K i value of (R)-MDMA is in the submicromolar range (K i = 0.63), which thus compares with the low micromolar concentrations found in the brain after administration of this drug [45,46] . In fact, the binding constant for this heteromeric receptor is lower than the K i value determined for the serotonin transporter, which is its main physiological target (24.5 μM) [40].…”
Section: Experimental Binding Affinity Of Mdma Enantiomersmentioning
confidence: 71%
“…Wagner et al reported a stereoespecific synthesis of amphetamines, although it was not applied to MDMA [44]. Recently, Huot et al published another synthesis of MDMA enantiomers by enantiospecific ring opening of aziridines with a Grignard reagent, even though the experimental details have not been described [40]. These synthetic approaches are not practical since they involve either low diastereoselectivities, costly preparation of the starting ketones or lack of experimental procedures.…”
Section: Synthesis Of Mdma Enantiomersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the MPTP-lesioned marmoset, S-MDMA (1:10 DAT/SERT ratio) significantly extended the duration of on-time after L-DOPA administration. However, this extension of L-DOPA antiparkinsonian benefit was marred by an exacerbation of dyskinesia (Huot et al, 2011). UWA-101 was the first equipotent DAT 5 SERT inhibitor to be developed for the treatment of PD.…”
Section: Dual Dat and Sert Inhibitorsmentioning
confidence: 99%